Comparative periodontoprotective effectiveness of diosmin or qvercetin in rats which received hormonal contraceptive - Levitsky, A. P.; Borisenko, A. V.; Vatankha, T. V. (Journal of Education, Health and Sport, 2017)
Aim: Determine periodontoprotective effectiveness of bioflavonoides diosmin and quercetin after introducing hormonal contraceptive. Methods: The rats received contraceptive (estradiol+drospirenon) during 30 days. Preparation of diosmin (“Normoven”) introduced per os in dose 84 mg/kg. Preparation of quercetin (“Quertulin”) introduced per os in dose 8 mg/kg. The activities of elastase and lysozyme were determined in gum and serum, the activities of alkaline (AlPh) and acid (AcPh) phosphatases, the contents of calcium and protein were determined in periodontal bone. The degree of bone atrophy of alveolar outgrowth was determined. Results: Was established that the introduction of the contraceptive decreased the mineralizing activity of the bone and increased the degree of atrophy of alveolar outgrowth. Simultaneous introduction of the bioflavonoides stimulated mineralizing activity and reduced the degree of atrophy of alveolar bone. Quercetin was more effective. Conclusion: Bioflavonoides have periodontoprotective activity after using hormonal contraceptive.